Copper‐Vapor‐Assisted Rapid Synthesis of Large AB‐Stacked Bilayer Graphene Domains on Cu‐Ni Alloy. Issue 15 (24th February 2016) - Yang, Chao; Wu, Tianru; Wang, Haomin; Zhang, Guanhua; Sun, Julong; Lu, Guangyuan; Niu, Tianchao; Li, Ang; Xie, Xiaoming; Jiang, Mianheng
Abstract : The synergic effects of Cu85Ni15 and the copper vapor evaporated from copper foil enabled the fast growth of a ≈300 μm bilayer graphene in ≈10 minutes. The copper vapor reduces the growth rate of the first graphene layer while the carbon dissolved in the alloy boosts the growth of the subsequently developed second graphene layer with an AB‐stacking order.